2004
DOI: 10.1200/jco.2004.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Consolidation Radiation After Complete Remission in Hodgkin's Disease Following Six Cycles of Doxorubicin, Bleomycin, Vinblastine, and Dacarbazine Chemotherapy: Is There a Need?

Abstract: Our study suggests that the addition of consolidation radiation helps improve the EFS and OS in patients achieving a complete remission after six cycles of ABVD chemotherapy, particularly in the younger age group and in patients with B symptoms and bulky and advanced disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
117
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(126 citation statements)
references
References 25 publications
5
117
0
4
Order By: Relevance
“…8 From 2002 to 2005, there were 4 published randomized clinical trials that compared CMT versus chemotherapy alone for the treatment of adult early-stage HL. [30][31][32][33] In each of these studies, disease control (ie, freedom from disease progression, freedom from treatment failure, or event-free survival) was better with CMT versus chemotherapy with absolute improvements ranging from 3% to 7%. Overall survival (OS) rates were similar in each study, although final analysis of the National Cancer Institute of Canada Clinical Trials Group (NCIC-CTG) Eastern Cooperative Oncology Group (ECOG) HD.6 study showed superior OS for chemotherapy alone at 12 years due to increased late events/toxicity in the CMT arm.…”
Section: Current Treatment Paradigms For Early-stage Hlmentioning
confidence: 99%
“…8 From 2002 to 2005, there were 4 published randomized clinical trials that compared CMT versus chemotherapy alone for the treatment of adult early-stage HL. [30][31][32][33] In each of these studies, disease control (ie, freedom from disease progression, freedom from treatment failure, or event-free survival) was better with CMT versus chemotherapy with absolute improvements ranging from 3% to 7%. Overall survival (OS) rates were similar in each study, although final analysis of the National Cancer Institute of Canada Clinical Trials Group (NCIC-CTG) Eastern Cooperative Oncology Group (ECOG) HD.6 study showed superior OS for chemotherapy alone at 12 years due to increased late events/toxicity in the CMT arm.…”
Section: Current Treatment Paradigms For Early-stage Hlmentioning
confidence: 99%
“…These results are similar to those described in the literature. (6)(7)(8)(9) Probabilities of OS and EFS were not statistically different when separated by staging as low or high risk (p = 0.402 and 0.969, respectively). This may be explained by the small sample size and because small variations in field strength and dose of radiotherapy treatment occurred as it was not adequately standardized, which may have interfered in the evaluation of EFS.…”
Section: Discussionmentioning
confidence: 98%
“…(9,22) This conduct does not seem appropriate for cases of bulky disease, there are few long-term evaluations of toxicity in protocols and, in cases of relapse, the child would receive even more drugs and radiotherapy resulting in increased toxicity. (23) A study conducted in India by Laskar et al (8) confirmed the need for the use of radiotherapy as consolidation treatment for HD. In this study, HL patients were randomized to receive six cycles of ABVD alone or in combination with radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Of the remaining four trials that have tested chemotherapy regimens that are associated with currently achievable optimal disease control (results shown in Table 4), two trials 19,20 report results of subset analyses from larger trials; in both reports, differences in the event-free or overall survivals of the randomized groups were not detected.…”
Section: Evolution To Current Standards Of Carementioning
confidence: 99%
“…A review of randomized trials testing chemotherapy alone in patients with limited-stage disease, and synopsis of potential limitations, is shown in Table 3. Eight randomized trials 14,[16][17][18][19][20][21][22] testing chemotherapy alone in patients with limited-stage disease have been reported, either as specific trials or as subset analyses of larger trials. Four of these trials tested chemotherapy that has been shown to be inferior to ABVD or its equivalent 14,[16][17][18] and thus these treatments cannot be recommended and the trials do not adequately test currently available chemotherapy as a single modality.…”
Section: Evolution To Current Standards Of Carementioning
confidence: 99%